Bulky Vehicles Recycling. Part 1 - Conditions for Recycling - Matuszewska, Anna; Wieczorek, Piotr; Samson-Bręk, Izabela (Studia Ecologiae et Bioethicae, 2020)
Recycling of end-of-life passenger vehicles is a well-known topic, and there are many literary reports in this regard. However, little information is available on the recycling of bulky vehicles, which determines the authors’ intention to present this issue. This article describes the loopholes that have prevented end-of-life vehicles from currently being recycled. The forms of recycling of these types of vehicles has been shown, and they are analogous to those for passenger cars. Also being presented are the causes of design changes in passenger cars and trucks, with the reasons for these changes being slightly different in bulky vehicles, than in passenger cars, and the article will discuss how these changes translate into recycling. Examples of actions taken by large vehicle manufacturers to meet the changes taking place in the economy, and implement the principles of the circular economy, in the field of recycling large-size vehicles, are also outlined.